Total pain and social suffering: marginalised Greenlanders' end-of-life in Denmark - Graven, Vibeke; Abrahams, Maja Bangsgaard; Pedersen, Tina (Frontiers in Sociology, 2023)
With a focus on socially marginalised Greenlanders in Denmark, this paper explores the significance of the concept of social suffering for the concept of total pain. Greenland is a former Danish colony and Greenlanders retain the right to Danish citizenship with all the benefits of access to the resources of Denmark as for any other Danish citizen. However, Greenlanders are overrepresented amongst the most socially disadvantaged in Denmark. They have a disproportionately high risk of an early death, often undiagnosed and untreated. This paper reports on research conducted with socially marginalised Greenlanders and some of the professionals who work with them. It interrogates the concept of total pain as developed by Cicely Saunders, the founder of modern palliative care. Saunders noted that pain at the end-of-life was not adequately explained by symptoms of a disease process because it was more like a situation that engulfed every aspect of the patient and those close to them; it included physical, psychological, spiritual and social dimensions. We agree with other scholars that the social dimension of the total pain experience is underexplored. By drawing on the theoretical and methodological lens of intersectionality, our work with marginalised Greenlanders has enabled us to describe the multiple and intersecting social forces that create social suffering for this group. This leads us to conclude that social suffering is not entirely an individual experience but a product of social harms and disadvantage, poverty, inequality and the various legacies of colonialism, which combine to place some citizens in a harmed condition. Our findings also draw us into a discussion with the concept of total pain and its neglect of the socially constructed nature of social suffering. We conclude by indicating ways in which the concept of total pain can be informed by a more thoroughgoing concept of social suffering. We conclude, with others, that there is a problem of inequity in the way that end-of-life care is currently distributed. Finally, we point to ways in which an understanding of social suffering can help to address the exclusion of some of the most vulnerable citizens from appropriate end-of-life care.